“Don’t sit back with the geraniums, get out”: The complexity of older women’s stories of sport participation - Horton, Sean; Dionigi, Rylee A.; Gard, Michael; Baker, Joseph; Weir, Patricia (Journal of Amateur Sport, 2018)
Encouraging sport participation is one method governments have utilized in the attempt to facilitate a more active senior citizenry. To date, investigations of seniors’ participation in sport has focused primarily on physiological variables, with fewer investigations devoted to psychosocial outcomes or what playing sport means to the older person in the context of wider health promotion discourses. Our qualitative investigation consisted of in-depth interviews with women competing in the 2013 World Masters Games. Interviews were conducted with 16 women ranging from 70 to 86 years of age and data were analysed within a post-structural framework. Three main themes emerged from the analysis: Multi-faceted benefits, Overcoming barriers, and Social roles. There is unquestionably complexity inherent to older females’ sport participation, in that our participants held views that both challenged and perpetuated some of the most common aging and gender stereotypes. Our findings critically analyse health promotion trajectories as they relate to older women and sport.